Multiple Low Energy Long Bone Fractures in the Setting of Rothmund-Thomson Syndrome. (5th November 2015) - Beckmann, Nicholas
Abstract : Rothmund-Thomson syndrome is a rare autosomal recessive genodermatosis characterized by a poikilodermatous rash starting in infancy as well as various skeletal anomalies, juvenile cataracts, and predisposition to certain cancers. Although Rothmund-Thomson syndrome is associated with diminished bone mineral density in addition to multiple skeletal abnormalities, there are few reports of the association with stress fractures or pathologic fractures in low energy trauma or delayed healing of fractures. Presented is a case of a young adult male with Rothmund-Thomson syndrome presenting with multiple episodes of long bone fractures caused by low energy trauma with one of the fractures exhibiting significantly delayed healing. The patient was also found to have an asymptomatic stress fracture of the lower extremity, another finding of Rothmund-Thomson syndrome rarely reported in the literature. A thorough review of the literature and comprehensive presentation of Rothmund-Thomson syndrome is provided in conjunction with our case.